2022
DOI: 10.1186/s13148-022-01242-6
|View full text |Cite
|
Sign up to set email alerts
|

A validation study of potential prognostic DNA methylation biomarkers in patients with acute myeloid leukemia using a custom DNA methylation sequencing panel

Abstract: Background Multiple studies have reported the prognostic impact of DNA methylation changes in acute myeloid leukemia (AML). However, these epigenetic markers have not been thoroughly validated and therefore are still not considered in clinical practice. Hence, we aimed to independently verify results of selected studies describing the relationship between DNA methylation of specific genes and their prognostic potential in predicting overall survival (OS) and event-free survival (EFS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Therefore, we designed a custom NGS-based DNA methylation panel comprising of loci/genes from selected studies as well as genes generally connected to AML pathogenesis such as HOX genes and WT1 . Apart from our recent study [ 7 ] that validated individual DNA methylation changes and utilized the same AML cohort as well as the DNA methylation sequencing panel, we now wanted to evaluate all potential epigenetic markers comprehensively at once.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we designed a custom NGS-based DNA methylation panel comprising of loci/genes from selected studies as well as genes generally connected to AML pathogenesis such as HOX genes and WT1 . Apart from our recent study [ 7 ] that validated individual DNA methylation changes and utilized the same AML cohort as well as the DNA methylation sequencing panel, we now wanted to evaluate all potential epigenetic markers comprehensively at once.…”
Section: Discussionmentioning
confidence: 99%
“…List of regions targeted by the methylation sequencing panel (according to the Human GRCh37/hg19 genome assembly) is shown in Additional file 1 . This DNA methylation panel was utilized also in our previous DNA methylation validation study [ 7 ]. Apart from the current study, we examined selected individual genes and validated their influence on AML prognosis separately.…”
Section: Introductionmentioning
confidence: 99%
“…Another group found that the methylation status of ATP11A, ITGAM, and ZNRF2 served as accurate prognostic markers in AML patients [ 100 ]. Sestakova et al analyzed previously-touted prognostic DNA methylation markers in AML across fourteen published studies, and confirmed methylation of four genes ( CEBPA, PBX3, LZTS2, and NR6A1 ) as predictive for longer survival, as well as two other genes ( DLX4 and GPX3 ) [ 101 ]. Despite some promising results, methylation patterns of these or other genes are not yet used in clinical practice for AML patients.…”
Section: The Future Of Biomarkers In Amlmentioning
confidence: 97%